Characteristics and linear stability analysis of RELAP5 two-fluid model for two-component, two-phase flow. (February 2021) - Saraswat, S.P.; Munshi, P.; Allison, C.
Highlights: Non-hyperbolic region of the two components and two phase mixture model. Effect of various thermal hydraulic parameters on the hyperbolicity TFM. Sensitivity of nuclear reactor safety analysis. Insight into the mathematical properties of the model. Effect of addition of bubble collision term on the linear stability. Abstract: The scope of this work comprises the study of the mathematical nature of the RELAP5 two-fluid model (TFM) for two-component (water and non-condensable gas (helium)) and two phases (liquid and vapor) mixture flows, and to predict the accuracy of the model under these flow conditions. The method of characteristics is applied to check the non-hyperbolic nature of conservation equations of RELAP5 for some sample fluid conditions. The sample problem selected here is a small break in helium-water heat exchanger primary tubes (containing high pressure and high-temperature helium gas) into the secondary shell (water) side high-temperature gas-cooled reactor, that causes mixing of helium-steam and liquid water and results in two-component two-phase flow. This sample problem is selected to address the RELAP5 model behavior and its sensitive nature under multi-component two-phase analysis. Linear stability analysis is also performed to check the error growth rates for the sample fluid conditions.